2002
DOI: 10.4049/jimmunol.168.8.3755
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Triggering Through 4-1BB Enables Th-Independent Priming of CTL in the Presence of an Intact CD28 Costimulatory Pathway

Abstract: Triggering of 4-1BB, a member of the TNFR family, through in vivo administration of agonistic anti-4-1BB Ab delivers a powerful costimulatory signal to CTL. We found this signal to effectively replace the need for CD4+ T cell help in the cross-priming of tumor-specific CTL immunity. Furthermore, 4-1BB Ab can convert an otherwise tolerogenic peptide vaccine into a formulation capable of efficient CTL priming. Initial activation of naive CTL can occur in the absence of 4-1BB costimulation, but this signal permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 25 publications
2
54
2
Order By: Relevance
“…Different tumor models and different treatment modalities have yielded different results. [29][30][31][32][33] Data herein was in sharp contrast to some investigators who claimed that 4-1BB signaling enable CTL priming in the absence of CD4 1 T cells, [29][30][31] but consistent with others who suggested that CD4…”
Section: Discussioncontrasting
confidence: 55%
“…Different tumor models and different treatment modalities have yielded different results. [29][30][31][32][33] Data herein was in sharp contrast to some investigators who claimed that 4-1BB signaling enable CTL priming in the absence of CD4 1 T cells, [29][30][31] but consistent with others who suggested that CD4…”
Section: Discussioncontrasting
confidence: 55%
“…Similarly, the reduced CTL response to influenza was shown to be at the level of persistence of T cells late in the primary response and to result in a weakened ability of the resultant memory CD8 cells to respond again to recall Ag (30,31). Complimentary data have also been described in systems using agonist Abs, in which provision of 4-1BB signals replaced the need for CD4 cells in an antitumor CD8 response that was normally dependent on CD4 help (32). These data clearly suggest parallels between 4-1BB and OX40 and indicate that each can play an important role in maintaining CD8 cell numbers and/or reactivity over time.…”
Section: Discussionmentioning
confidence: 85%
“…However, the location of the 4-1BBL in the unimmunized mouse remains unknown. Although 4-1BBL has been reported on APC following activation with LPS or anti-CD40 (51)(52)(53)(54)(55), it has been difficult to detect on in vivo-activated APC following influenza or lymphocytic choriomeningitis virus infection (M. A. DeBenedette and T. H. Watts, unpublished results). To test whether IL-15 might induce 4-1BBL as well as its receptor, we added IL-15 to collagenase-treated splenocytes and bone marrow-derived immature dendritic cells, but 4-1BBL was not detected (data not shown).…”
Section: Cd8mentioning
confidence: 99%